Three-dimensional analysis of palate roughness as a biometric identification tool (Revista Contexto & Saúde, 2024)
Palatal wrinkles are elevations of the oral mucosa that cover the palatine process and are located on the maxillary bone. Because its anatomy is immutable and unique to each individual, the method of human identification using palatal wrinkles has a lot of potential to become indisputable. Currently, with the incorporation of new technologies in dentistry, three-dimensional analysis of palatal wrinkles using scans has become a reality. The aim of this study was to analyze the applicability of three-dimensional analysis of palatal wrinkles for human identification, through the observation of 3D images resulting from digital scanning. This is an experimental study with a qualitative-quantitative approach, whose sample consisted of the scanning of 50 plaster models, where three-dimensional images were generated, the classifications used were with the techniques of Silva (1938), Carrea, (1937) and Bassauri (1961). The 3D scanning was done by a software system from the Zirkonzahn company, using the s600 arti scanner, and the wrinkle analysis was carried out by the Meshmixer program. When used separately, the techniques were not sufficient for individual human identification. However, the individual code generated by combining the three methods proved to be unique for each model used. Thus, the results obtained proved the applicability of three-dimensional analysis of palatal wrinkles for human identification.
Keywords: Human Identification; Hard Palate; Forensic Odontology